2023
DOI: 10.15240/tul/001/2023-1-003
|View full text |Cite
|
Sign up to set email alerts
|

Differences and Similarities in Patterns of Ageing Society in the European Union

Abstract: Population ageing is a demographic issue that emphasises the need to be interested in the lives of the most vulnerable population group: the elderly population. The paper investigates the ageing process and their relations among the European Union member countries from 2009 to 2019. These countries are assessed and dispersed to the appropriate clusters according to several indicators related to the areas that affect the lives of the elderly population: namely, the health status, the labour market conditions, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Other research has shown that an individual's financial well-being is strongly related to overall well-being when many faces financial problems. It leads to adverse welfare effects, both now and in the future (Brüggen et al, 2017;Xiao et al, 2022;Tsouli, 2022;Kočanová et al, 2023). Van Praag et al (2003) confirmed that a healthy spending and savings balance is essential for sustaining long-term financial and personal well-being.…”
Section: Discussionmentioning
confidence: 96%
“…Other research has shown that an individual's financial well-being is strongly related to overall well-being when many faces financial problems. It leads to adverse welfare effects, both now and in the future (Brüggen et al, 2017;Xiao et al, 2022;Tsouli, 2022;Kočanová et al, 2023). Van Praag et al (2003) confirmed that a healthy spending and savings balance is essential for sustaining long-term financial and personal well-being.…”
Section: Discussionmentioning
confidence: 96%
“…In order to perform the analysis, this method requires selecting the number of clusters prior to the analysis. Consequently, taking into consideration studies with similar logic (Kočanová, Kováč, Serzhanov, & Buleca, 2023;Zhang, et al, 2022;Tobis, et al, 2021) and the size of Croatia, the analysis is set to be performed with three cluster groups.…”
Section: Methodsmentioning
confidence: 99%